Immunogenicity and Safety of a Novel 13-Valent Pneumococcal Vaccine in Healthy Chinese Infants and Toddlers - Zhao, Yuliang; Li, Guohua; Xia, Shengli; Ye, Qiang; Yuan, Lin; Li, Hong; Li, Jiangjiao; Chen, Jingjing; Yang, Shuyuan; Jiang, Zhiwei; Zhao, Guoqing; Li, Rongcheng; et al. (Frontiers in Microbiology, 2022)
Background To determine the non-inferiority of the seven common serotypes (4, 6B, 9V, 14, 18C, 19F, and 23F) in the 13-valent pneumococcal conjugate vaccine (PCV13) with each serotype conjugated to a tetanus toxoid carrier protein and adsorbed on aluminum phosphate and the superiority of its six additional serotypes (1, 3, 5, 6A, 7F, and 19A) to the serotypes in the PCV7. Methods Participants were evenly randomized in a 1:1 ratio into either the PCV13 or PCV7 groups, to receive three doses of the vaccine at the age of 3, 4, and 5 months, respectively, and a booster dose between 12 and 15 months of age. Serotype-specific antibodies were measured using a standardized enzyme-linked immunosorbent assay (ELISA) and opsonophagocytic activity (OPA) microcolony assay method. Results A total of 1,040 healthy infants were enrolled. All the seven common serotypes in the PCV13 were non-inferior to those in the PCV7 in terms of the serotype-specific IgG production induced; however, non-inferiority was not shown for serotype 6B after the infant series. The proportion of subjects who reached OPA antibody titers ≥ 1:8 in the PCV13 group was 89.25% or higher. Local reactions and systemic events were mild or moderate in severity and similar between the two groups. No new safety signals were observed. Conclusion The newly developed PCV13 was immunogenic for all serotypes and had a comparable safety profile to the marketed PCV7.